Memetakan Tantangan Pendidikan Kristiani bagi Remaja Menghadapi Gaya Hidup Era Society 5.0 - Saputro, Joko; Missa, Antonius; Sitinjak, Abraham Pontius (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2022)
This paper describes the impact of the emergence of Society 5.0, a new civilization in the information age. Today humans are faced with a completely new situation in the arena of history. With the presence of Society 5.0, it is hoped that the community can solve various social challenges and problems by utilizing various innovations born in the Industrial Revolution 4.0. This is a new civilization, a new world, a time in which a human-centered society balances economic progress with the resolution of social problems by a system that integrates cyberspace and physical space. Society 5.0 will balance economic development and solve social problems. Then, is it true that Society 5.0 will bring progress for the benefit of many people? Civilization Society 5.0 is an answer as well as new challenges that have emerged as a result of the era of the Industrial Revolution 4.0, which was accompanied by disruption marked by a world full of turmoil, uncertainty, complexity, and ambiguity, of course, it is a new hope for families to educate their children so as not to experience disruption. This research method is the theological method in Christian religious education. Through this paper, the authors put conceptual ideas for Christian religious education, especially in building a harmonious family, and several solutions to the challenges of the civilization of Society 5.0.  AbstrakDengan kehadiran Society 5.0 diharapkan masyarakat dapat menyelesaikan berbagai tantangan dan permasalahan sosial dengan memanfaatkan berbagai inovasi yang lahir di era Revolusi industri 4.0. Inilah sebuah peradaban dunia baru, sebuah masa di mana masyarakat berpusat pada manusia yang menyeimbangkan kemajuan ekonomi dengan penyelesaian masalah sosial oleh sistem yang mengintegrasikan ruang dunia maya dan ruang fisik. Lalu, apakah benar bahwa Society 5.0 akan membawa kemajuan bagi kemaslahatan orang banyak? Tulisan ini bertujuan mengurai dampak yang ditimbulkan akibat dari kemunculan Society 5.0 yang merupakan peradaban baru di era informasi. Metode penelitian ini adalah metode analitis teologis bidang pendidikan agama Kristen. Melalui tulisan ini penulis menaruh gagasan konseptual bagi Pendidikan agama Kristen khususnya dalam membangun keluarga harmonis, serta beberapa solusi dalam menyambut tantangan yang didapat dari peradaban Society 5.0. Hasil penelitian ini adalah Peradaban Society 5.0 merupakan jawaban sekaligus tantangan baru yang muncul akibat era Revolusi Industri 4.0 yang dibarengi disrupsi yang ditandai dunia yang penuh gejolak, ketidakpastian, kompleksitas, dan ambiguitas, tentu saja itu merupakan harapan baru bagi keluarga-keluarga untuk mendidik anak-anaknya agar tidak mengalami disrupsi. Society 5.0 menyeimbangkan pembangunan ekonomi dan menyelesaikan masalah sosial.